Qur’anic Stories As A Source Of The Prophet’s Biography - Jaafar Najmadin Ali Gwan; Mahdi Amen Hadi (QALAAI ZANIST JOURNAL, 2020)
The German orientalist (RUDI PARET) used the Qur’anic stories as a source for writing the biography, and he considered that the experience of the Prophet Muhammad (PBH), may God’s prayers and peace be upon him, was an extension of the experience of previous prophets, as well as his people with their people and supporters with their supporters, and from here he tried to search for similarities between his life and their lives in order to find common points in what happened to the Prophet from Through the examples mentioned in the case of the ex-ex, and it was concluded from that to clarify fixed events in the biography and document it through the Qur’anic stories, which paves the way for researchers to document events that were not proven in the Holy Qur’an, or to modify events that are widely interpreted differently.